Kemampuan Beradaptasi Sosial Mahasiswa Batak di Lingkungan Yogyakarta - Anggi Agustin Kaban; Yohanes Heri Widodo (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The purpose of this research is: 1) to know the level of Batak students' adaptability at Yogyakarta, 2) given the ability to adapt any off-optimal (low) Batak students that could be suggested as a topic of guidance. It's addressed to Batak students at Yogyakarta. 112 Batak students. The gauge we use is the scale of adaptability. Variable data gathering is adaptable variables. Valid items have 34 of the 50 items. Valid item score: 0.938. Research found: 1) the Batak college's social adaptability level is high. This was demonstrated from the total of subjects filling out the 112 respondents who answered the questionnaires there are 16 (14%) students with very high adaptive capabilities, 53 (47%) with high-adapted abilities, 38 (34%) students with moderate adaptation capabilities, 5 (4%) of respondents with low adaptive capabilities and no category identified as very low. 2) got an item from a low adaptability variable. From the item proposed on guidance topic: "a strategy to build better relationships through empathy."